2011
DOI: 10.1055/s-0030-1256128
|View full text |Cite
|
Sign up to set email alerts
|

Natural-orifice transluminal endoscopic surgery (NOTES) in Europe: summary of the working group reports of the Euro-NOTES meeting 2010

Abstract: The fourth Euro-NOTES workshop took place in September 2010 and focused on enabling intensive scientific dialogue and interaction between participants to discuss the state of the practice and development of natural-orifice transluminal endoscopic surgery (NOTES) in Europe. Five working groups were formed, consisting of participants with varying scientific and medical backgrounds. Each group was assigned to an important topic: the correct strategy for dealing with bacterial contamination and related complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 6 publications
0
39
0
1
Order By: Relevance
“…"Pure NOTES" is not yet established in routine surgery to date; however, with the aim of reducing surgical trauma, hybrid NOTES could be a valuable option to bring NOTES into clinical practice. Recent studies have demonstrated hybrid NOTES cholecystectomy to be feasible and safe in routine clinical practice [5]. In contrast, single incision laparoscopic surgery has reached the level of limited clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…"Pure NOTES" is not yet established in routine surgery to date; however, with the aim of reducing surgical trauma, hybrid NOTES could be a valuable option to bring NOTES into clinical practice. Recent studies have demonstrated hybrid NOTES cholecystectomy to be feasible and safe in routine clinical practice [5]. In contrast, single incision laparoscopic surgery has reached the level of limited clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Next to the general feasibility and safety of NOTES, educational aspects must be evaluated before the new technique can be introduced into clinical practice [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to classical open surgery the surgeon faces the problem of limited dexterity regarding the control of the instruments in minimally invasive surgery. Especially during ESD, where only one single instrument can be used for active manipulation [7]. The ideal solution would be a system that allows the surgeon to control two instruments independently in order to oppose them.…”
Section: Actuation and Sterile Couplingmentioning
confidence: 99%
“…The ideal solution would be a system that allows the surgeon to control two instruments independently in order to oppose them. This configuration is the so-called triangulation [7], [8]. …”
Section: Actuation and Sterile Couplingmentioning
confidence: 99%